7-Hydroxycassine: A new 2,6-dialkylpiperidin-3-ol alkaloid and other constituents isolated from flowers and fruits of senna spectabilis (Fabaceae) - Viegas, Cláudio; Pivatto, Marcos; De Rezende, Amanda [UNESP]; Hamerski, Lidilhone [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2013)
The phytochemical study of flowers and green fruits of Senna spectabilis furnished a new substituted 2,6-dialkylpiperidin-3-ol alkaloid, named (-)-7-hydroxycassine, along with five known piperidine alkaloids: (-)-cassine, (-)-spectaline, (-)-3-O-acetylspectaline, (-)-7-hydroxyspectaline and (-)-iso-6-spectaline. In addition to non-alkaloidal, chemical constituents from other chemical classes were also identified, including the steroid β-sitosterol, the flavonoids luteolin and 3-methoxyluteolin, the triterpene betulinic acid and trans-cinnamic acid. To our knowledge, compounds are being reported for the first time in this species. © 2013 Sociedade Brasileira de Quimica.
Keywords: (-)-7-hydroxycassine; Piperidine alkaloids; Senna spectabilis